Thallium-doped sulphate potassium crystals as materials for radiation detectors - Myrzakhmet, M.; Nikl, M.; Jary, V.; Dalelkhan, B.; Zhanabergenov, A. (Functional Materials, 2013)
Luminescence characteristics of potassium sulphate (K₂SO₄) crystals doped with thallium were studied. Crystals were grown from water solution at slightly elevated temperature. The nature and properties of the luminescence centres in these crystals have been determined. The main monovalent thallium luminescence centres show the absorption peak at 216 nm and emission one peaking at 285 nm at room temperature. Thallium is substituting potassium which has two different positions in K₂SO₄ structure. Consequently, two different Tl⁺ centers were found for thallium centers in these crystals and the third center includes an unspecified perturbation agent nearby. Tl⁺ centers differ in radiative lifetime at low temperatures and in temperature dependence of decay times measured within 8—300 K.